Vaping behaviour patterns and daily blood pressure and heart rate variation: a brief report - Susan D. Mueller; Geraldine R. Britton; Gary D. James; Pamela Stewart Fahs (Taylor & Francis Group, 2021)
Background Vaping, the use of an electronic device to deliver a drug-infused aerosol has become an increasingly popular way to consume nicotine since its introduction to the market in the early 2000s. Despite the differences in consumption patterns relative to combustible tobacco, the impact of ad libitum nicotine vaping on cardiovascular response has not been thoroughly studied. Subject and methods This research was conducted on vapers (n = 17) and smokers (n = 14) who represent a subsample of a larger study that explored the relationship between nicotine use, activities of daily living and 24-hour cardiovascular response using Spacelabs ambulatory blood pressure monitors. These data were analysed via ANOVA models and t-tests using SPSS 25.0 for Macintosh. Results Vapers consumed nicotine significantly more frequently than did smokers, at 48.2% and 18.1% of every 15-minute waking measurement, respectively (p = 0.000). The act of nicotine consumption, rather than the mode of delivery, was significantly associated with increases in systolic, diastolic, mean arterial pressure, and heart rate readings. There was no difference in the mean amplitude of response to nicotine between vapers and smokers. Conclusions This study's strong statistical findings, visually evident on ambulatory blood pressure monitor reports, demonstrated that ad libitum nicotine consumption has an acute, dose-dependent effect on cardiovascular response regardless of whether it is smoked or vaped. However, since vapers consumed nicotine more frequently, future studies should be conducted with larger sample sizes, and controlled for age and comorbidities to improve statistical strength. Implications This pilot study reveals that, when ad lib consumption is documented and measured, vaping has unique and potentially harmful effects on blood pressure, pulse, and mean arterial pressure. Because nicotine is consumed for much longer stretches, vapers have fewer rest periods between nicotine doses.